Independent age estimates resolve the controversy of ancient human footprints at White Sands - Pigati, Jeffrey S.; Springer, Kathleen B.; Honke, Jeffrey S.; Wahl, David; Champagne, Marie R.; ZIMMERMAN, SUSAN R. H.; Gray, Harrison J.; Santucci, Vincent L.; Odess, Daniel; Bustos, David; Bennett, Matthew R. (Science, 2023)
Human footprints at White Sands National Park, New Mexico, USA, reportedly date to between ~23,000 and 21,000 years ago according to radiocarbon dating of seeds from the aquatic plant Ruppia cirrhosa. These ages remain controversial because of potential old carbon reservoir effects that could compromise their accuracy. We present new calibrated 14C ages of terrestrial pollen collected from the same stratigraphic horizons as those of the Ruppia seeds, along with optically stimulated luminescence ages of sediments from within the human footprint–bearing sequence, to evaluate the veracity of the seed ages. The results show that the chronologic framework originally established for the White Sands footprints is robust and reaffirm that humans were present in North America during the Last Glacial Maximum.
Publisher: American Association for the Advancement of Science

Evidence of humans in North America during the Last Glacial Maximum - Bennett, Matthew R.; Bustos, David; Pigati, Jeffrey S.; Springer, Kathleen B.; Urban, Thomas M.; Holliday, Vance T.; Reynolds, Sally C.; Budka, Marcin; Honke, Jeffrey S.; Hudson, Adam M.; Fenerty, Brendan; Connelly, Clare; et al. (Science, 2021)
Archaeologists and researchers in allied fields have long sought to understand human colonization of North America. Questions remain about when and how people migrated, where they originated, and how their arrival affected the established fauna and landscape. Here, we present evidence from excavated surfaces in White Sands National Park (New Mexico, United States), where multiple in situ human footprints are stratigraphically constrained and bracketed by seed layers that yield calibrated radiocarbon ages between ~23 and 21 thousand years ago. These findings confirm the presence of humans in North America during the Last Glacial Maximum, adding evidence to the antiquity of human colonization of the Americas and providing a temporal range extension for the coexistence of early inhabitants and Pleistocene megafauna.
Publisher: American Association for the Advancement of Science